A Criminological Review: Exploring Community Perception of Juvenile Delinquency in Panenjoan Village - Eki Furqon; Alycia Risaldy Halim; Fuad Sirojul Huda; Nisrina Agustini; Syifa Aulia Nur Fadlilah; Muhamad Farhan Al Amien; Ratri Yulianingsari Negoro; Santomi Santomi; Yunita Yunita; Aqila Zahra; Diska Eunike; Aisa Aulina (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2022)
Juvenile delinquency is becoming one of the urgencies that must be considered by us, especially in Panenjoan Village. With the development of the times, these teenagers will get convenience in any case. Including to do negative things. As is being hotly reported on television, there are a lot of juvenile delinquency acts that are troubling the surrounding residents. The purpose of this study is to find out what juvenile delinquency occurs in Panenjoan Village as well as to know the perception of the community regarding the occurrence of juvenile delinquency which is quite large in percentage. This study uses the Community Education method by conducting socialization related to juvenile delinquency with the theme